Apocynin, an NADPH oxidase inhibitor, suppresses rat prostate carcinogenesis - Shugo Suzuki (2018)
Recent evidence suggests that oxidative stress contributes to the pathogenesis of prostate cancer. The present study focused on the effect of apocynin, an inhibitor of NADPH oxidase, on prostate carcinogenesis using the transgenic rat for adenocarcinoma of prostate (TRAP) model. There were no toxic effects with apocynin treatment. The percentages and numbers of carcinomas in both the ventral and lateral prostate were significantly reduced by apocynin treatment, with dose dependence. Reduction of reactive oxygen species by apocynin was confirmed by immunohistochemistry of 8-OHdG and dihydroethidium staining. Positivity of Ki67 was significantly reduced by apocynin treatment, and downregulation of clusterin expression, as well as inactivation of the MEK-ERK1/2 pathway, was a feature of the apocynin treated groups. In human prostate cancer cell line LNCaP, apocynin also inhibited reactive oxygen species production and blocked cell growth by inducing G0/G1 arrest with downregulation of clusterin and cyclin D1. These data suggest that apocynin possesses chemopreventive potential against prostate cancer. © 2013 Japanese Cancer Association.